2007
DOI: 10.1021/ol7016966
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Control over the Conformation of the Alkyne−Aryl Bond by the Introduction of Cationic Charge

Abstract: A novel arylene-ethynylene molecule has been synthesized. This molecule is more stable in a coplanar form than in a twisted form as in the cases of typical arylene-ethynylene molecules. When the cationic charge was introduced into the pi-conjugated system, the perpendicularly twisted form became more stable than the coplanar state. The conformational change was controlled by introduction and removal of cationic charge, confirmed by the absorption and fluorescence spectroscopy and DFT calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In that report, the optical properties of π‐conjugated polymers were modulated by introducing imidazolium units in the main chain compared to the corresponding imidazole‐based conjugated polymers depending on partnering aryl units. That is, for a phenyleneethynylene‐based π‐conjugated polymer, characteristic blue shift was observed both for absorption and fluorescence bands on the quaternization of imidazole‐1,5‐yl units to imidazolium, which was attributed to the distortion on the conjugated main chain on the introduction of cationic charge 45. On the other hand, thienyleneethynylene‐based π‐conjugated polymers showed a characteristic red shift by converting the imidazole units to cationic imidazolium due to the formation of donor–acceptor (D–A) structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that report, the optical properties of π‐conjugated polymers were modulated by introducing imidazolium units in the main chain compared to the corresponding imidazole‐based conjugated polymers depending on partnering aryl units. That is, for a phenyleneethynylene‐based π‐conjugated polymer, characteristic blue shift was observed both for absorption and fluorescence bands on the quaternization of imidazole‐1,5‐yl units to imidazolium, which was attributed to the distortion on the conjugated main chain on the introduction of cationic charge 45. On the other hand, thienyleneethynylene‐based π‐conjugated polymers showed a characteristic red shift by converting the imidazole units to cationic imidazolium due to the formation of donor–acceptor (D–A) structures.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole is an aromatic heterocycle containing imine nitrogen, which acts as an important building unit for biomolecules and has attractive chemical properties such as formation of coordination compounds and effective hydrogen bonding 43, 44. Hence, it is considered to be a building unit for π‐conjugated molecular and polymer systems in recent studies 45, 46. Imidazole is easily converted into imidazolium cation, which has a cationic charge by protonation or quaternization of the N ‐position similar to thiazole and pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…[5, 6] It is also widely accepted that a flexible CP chain can be considered as an ensemble of chromophores of different lengths because of the conformational disorder of large torsion angles, [7] and, consequently, excitation delocalization is dominated by resonance energy transfer (ET; Förster-type energy transfer or hopping) among the chromophores. [8] Recent quantum chemical calculations further revealed that a medium torsion angle ( 508) is sufficient to confine the excitation within a short subunit of CPs.[9] Nevertheless, the concept of torsion-induced localization of excitation and the resulting intrachain ET have not yet been verified with structurally well-defined conjugated oligomers, presumably because of the difficulties in conformational control [10] and in prevention of excited-state torsional relaxation [11] for the twisted conformers.Our recent work [12,13] on the pentiptycene-derived oligo(p-phenyleneethynylene)s (OPEs) 1 and 2 have revealed that these systems are excellent candidates for investigation of the concept of torsion-induced localization of excitation. Two distinct fluorescing states, which correspond to excited conformers of small and large torsion angles, have been identified for both 1 and 2.…”
mentioning
confidence: 99%
“…[8] Recent quantum chemical calculations further revealed that a medium torsion angle ( 508) is sufficient to confine the excitation within a short subunit of CPs. [9] Nevertheless, the concept of torsion-induced localization of excitation and the resulting intrachain ET have not yet been verified with structurally well-defined conjugated oligomers, presumably because of the difficulties in conformational control [10] and in prevention of excited-state torsional relaxation [11] for the twisted conformers.Our recent work [12,13] on the pentiptycene-derived oligo(p-phenyleneethynylene)s (OPEs) 1 and 2 have revealed that these systems are excellent candidates for investigation of the concept of torsion-induced localization of excitation. Two distinct fluorescing states, which correspond to excited conformers of small and large torsion angles, have been identified for both 1 and 2.…”
mentioning
confidence: 99%
“…[8] Recent quantum chemical calculations further revealed that a medium torsion angle ( 508) is sufficient to confine the excitation within a short subunit of CPs. [9] Nevertheless, the concept of torsion-induced localization of excitation and the resulting intrachain ET have not yet been verified with structurally well-defined conjugated oligomers, presumably because of the difficulties in conformational control [10] and in prevention of excited-state torsional relaxation [11] for the twisted conformers.…”
mentioning
confidence: 99%